Health Care Chaplains and their Role on Institutional Ethics Committees: An Australia Study - Carey, Lindsay B. (Journal of religion and health, 2010)
This paper presents the results of the largest Australian pastoral study concerning the perceptions of health care chaplains about their involvement on hospital research ethics committees (also known in some contexts as institutional ethics committees). Survey results from over 300 Australian health care chaplains indicated that nearly 90% of chaplains believed there was merit in chaplains serving on hospital research ethics committees, yet only a minority (22.7%) had ever participated on such committees. Data from in-depth interviews is also presented exploring the reasons for the lack of participation and the varying opinions regarding the role, appropriateness, and value of chaplains on ethics committees. Some implications of this study with respect to chaplaincy, hospital research ethics committees, health care institutions, ecclesiastical institutions, and government responsibilities are discussed.